Técnicas de PWM na operação de conversores em microrredes considerando a prestação de serviços de suporte - Olivo, Douglas (2024)
In recent years, the insertion of Distributed Energy Resources (DERs) in electrical systems has grown. As a solution to better integrate them, Microgrids (MGs) emerge, based mainly on renewable energy sources connected through Power Electronic Converters (PEC) to loads and the main grid. These converters can be explored to, in addition to supplying energy, provide ancillary services of interest, such as reactive support. In this sense, several PWM techniques enable better use of the voltage on the DC side of the converter and there is a gap in the literature for a broader investigation that relates the implementation of these PWM strategies to the provision of support services, especially in the context of MGs, with more than one converter operating in parallel. The present work aims to verify to what extent the use of PWM techniques that allow greater use of DC voltage can contribute to the use of converters in the provision of support services. To this end, a test system, based on the MG laboratory of the UNIOESTE campus in Foz do Iguaçu, is used to carry out simulations that allow studying the behavior of converters in providing reactive power support using the sinusoidal PWM (SPWM), the Third Harmonic Injection PWM (THIPWM) and the Space Vector PWM (SVPWM). Different operating scenarios are simulated, considering islanding and reactive demand events and varying the voltage available on the DC bus and the PWM strategy used. For each of the scenarios, frequency, voltage and power of the converters are evaluated, in addition to the capability curve with the converter power limits and the operating point for the simulated scenario. Capability curves comparing the operating regions for the different PWM techniques for the same DC bus voltage are also presented. From the simulations, it is observed that techniques such as THIPWM and SVPWM give the converter greater margins for modulation within the linear range, compared to the commonly used SPWM, representing a gain of 15% in maximum output voltage. This implies an increase in the feasible operating region of the capability curve, which translates into a greater reactive support capacity without compromising the supply of active power, demonstrating that the use of a PWM technique that allows a greater utilization of the DC bus voltage contributes to better performance of converters in ancillary services provision in MGs.